EFECTO DE LOS EXTRACTOS VEGETALES SOBRE EL DESARROLLO LARVAL DE Spodoptera frugiperda EN CONDICIONES DE LABORATORIO - Boza Ortiz , Gabriel Alejandro (2024)
The fall armyworm is a polyphagous species that mainly affects corn and sorghum crops. During the first days of plant development, the larva can act by cutting the plant close to the ground or partially or completely defoliating it, which causes the death of the plant.